A’matoang di Desa Bontotiro Kecamatan Rumbia Kabupaten Jeneponto - Riska R. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to determine the process of implementing A'matoang in Bontotiro Village, Rumbia District, Jeneponto Regency. This research uses a type of qualitative research with a descriptive approach. Data collection techniques were obtained through observation, interviews, documents and documentation involving several informants. The results of this study indicate that the process of implementing A'matoang in Bontotiro Village, Rumbia District, Jeneponto Regency consists of several stages, namely the preparation and implementation stages. At the preparatory stage is the stage of preparing the items to be brought when going to do A'matoang such as cupboards, sarongs, clothes, pots and bags, then the bride is escorted to the man's house, after arriving at the man's house the items inheritance left to the male side of the family. Furthermore, the implementation stage begins with the bride visiting her parents-in-law's house and handing over the luggage to the male family which is carried out by the bride.